Forging diaspora : Afro-Cubans and African Americans in a world of empire and Jim Crow - Guridy, Frank Andre (Envisioning Cuba., 2010)
Drawing on archival sources in both countries, Guridy traces four encounters between Afro-Cubans and African Americans. These hidden histories of cultural interaction--of Cuban students attending Booker T. Washington's Tuskegee Institute, the rise of Garveyism, the Havana-Harlem cultural connection during the Harlem Renaissance and Afro-Cubanism movement, and the creation of black travel networks during the Good Neighbor and early Cold War eras--illustrate the significance of cross-national linkages to the ways both Afro-descended populations negotiated the entangled processes of U.S. imperial.